VALUE ENGINEERING APPLICATION FOR ELEMENT ANALYSIS OF HEAVY EQUIPMENT EVACUATION TO GET HIGHER ACTIVITY VALUE - Soerjodibroto, Mulyanto; Putri, Nadila Guspani (Jurnal Inovasi Pertambangan dan Lingkungan, 2023)
The safety of workers and equipment from the dangers of flyrock blasting is an absolute must. The purpose of this safeguard is in line with the K3 and K Operational Mining principles as emphasized in the Good Mining Practice guidelines. It is undeniable that in order to meet these safety requirements, it is necessary to sacrifice costs as well as loss of equipment production  hours. With reference to the principles of Value Engineering Analysis, research was carried out in an effort to reduce these sacrifices by reducing the farthest flyrock ejection distance of  bench overburden blasting  at PT. Antareja Mahada Makmur site in East Kalimantan  without violating the safety requirements as meant in the Minister of ESDM Decree no. 1827/2018 Attachment 2 page 79 points (ix). The research was carried out by modifying the parameters of the detonation ladder, especially those related to the explosives factor, to obtain safe distance from the farthest ejection of flyrock which is smaller than the 300 meter requirement. From the experimental series, it was obtained that the safe distance from the farthest ejection of flyrock is  150 meters as a reference for heavy equipment evacuation. This brings benefits to the company in the form of reducing sacrifices up to ± 50% from the previous without reducing the required Safety Value. Keywords : Flyrock , Safe distance , Value Engineering.